Method of Developing Speed and Strength Abilities of Young Boxers 12-13 Years Old - A. B. Zhuraev (Researchparks Publishing, 2022)
This article examines the features of the development and improvement of the speed and strength qualities of young boxers aged 12-13 years, as well as the results obtained during the pedagogical experiment.